An epidemiological study on complications of total laparoscopic hysterectomy in obese vs. non-obese patients at tertiary care centre - Sirsam, Shyamkumar S.; Dhakne, Madhuri; Shah, Manthan M.; Patil, Bhupendra V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Total Laparoscopic Hysterectomy (TLH) is now the preferred approach for benign gynecological conditions due to reduced morbidity and faster recovery. However, obesity remains a challenge influencing surgical outcomes and complication rates. This study aimed to compare intraoperative and postoperative complications of TLH in obese versus non-obese women. Methods: A comparative observational study was conducted at the Department of Obstetrics and Gynaecology, Government Medical College, Akola, Maharashtra, a tertiary care centre, including 146 women undergoing TLH. Participants were divided into obese (BMI ≥30 kg/m²; n=82) and non-obese (BMI <30 kg/m²; n=64) groups. Intraoperative and postoperative parameters, including blood loss, complications, operative time, and hospital stay, were recorded and analysed using the chi-square test and t-tests. Results: The mean age of participants was 49.8±11.7 years. Obese patients had significantly higher intraoperative blood loss (306.0±20.4 mL vs 270.8±45.4 mL; p<0.001). Mean operative duration (117.8 vs 113.3 minutes; p=0.167) and hospital stay (2.6 vs 2.5 days; p=0.477) did not differ significantly. Most surgeries (83%) were completed without complications. Bleeding (8%) and conversion to laparotomy (5%) were the common intraoperative events. Postoperative vault infections (9% vs 2%; p=0.032) and port-site infections (4% vs 0%; p=0.022) were more frequent among obese women. Conclusions: TLH can be safely performed in obese women with outcomes comparable to non-obese patients. Although obese women had higher minor wound-related complications, major intraoperative events were not significantly different.